2021
DOI: 10.1038/s41598-021-91808-w
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for stochastic resonance effects on standing balance when applying noisy galvanic vestibular stimulation in young healthy adults

Abstract: Noisy galvanic vestibular stimulation (nGVS) at imperceptible levels has been shown to reduce body sway. This reduction was commonly attributed to the mechanism of stochastic resonance (SR). However, it has never been explicitly tested whether nGVS-induced effects on body sway consistently follow a SR-like bell-shaped performance curve with maximal reductions in a particular range of noise intensities. To test this, body sway in 21 young healthy participants was measured during varying nGVS amplitudes while st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…A previous study demonstrated that nGVS effectively reduces the vestibular motion perception thresholds in the presence of low-intensity stochastic vestibular stimuli (Galvan-Garza et al, 2018 ). However, another study reported that nGVS effects on body sway were incompatible with the stochastic resonance in healthy young adults (Assländer et al, 2021 ). Future studies should clarify whether the modulation of EMG activity and angular velocity is induced by the nGVS amplitude following stochastic resonance.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that nGVS effectively reduces the vestibular motion perception thresholds in the presence of low-intensity stochastic vestibular stimuli (Galvan-Garza et al, 2018 ). However, another study reported that nGVS effects on body sway were incompatible with the stochastic resonance in healthy young adults (Assländer et al, 2021 ). Future studies should clarify whether the modulation of EMG activity and angular velocity is induced by the nGVS amplitude following stochastic resonance.…”
Section: Discussionmentioning
confidence: 99%
“…In the one study that investigated people with BVP standing on foam with their eyes closed nGVS did not have a significant effect on sway velocity (Sprenger et al, 2020). This pattern has also been seen in healthy young adults (Inukai et al, 2020a,b;Matsugi et al, 2020;Asslander et al, 2021), and while overall Mulavara et al (2011) and Goel et al (2015) concluded nGVS improved postural stability, when we look at individual participant results, only approximately half the participants in these two studies had reduced sway velocity standing on foam with their eyes closed. While it seems intuitive that augmenting the vestibular system should improve balance when the task is dependent on vestibular inputs, there are several reasons why we may not see the anticipated improvement in healthy populations or in people with BVP.…”
Section: Standing Balancementioning
confidence: 69%
“…These initial studies have often looked at multiple intensities, yet only reported on the intensity related to optimal performance (Goel et al, 2015 ; Mulavara et al, 2015 ; Fujimoto et al, 2016 ; Iwasaki et al, 2018 ) or have examined one intensity compared to sham stimulation (Inukai et al, 2018a , b , 2020a , b , c ; Nooristani et al, 2019a , b ; Matsugi et al, 2020 ). Research investigating performance alterations across a broad spectrum of stimulation intensities to account for the presence or absence of stimulation-induced stochastic resonance is starting to fill these gaps in our knowledge (Galvan-Garza et al, 2018 ; Asslander et al, 2021 ; Wuehr et al, 2022b ). Investigation of parameter induced patterns of performance across a range of frequencies and amplitudes in people with reduced vestibular function or high baseline postural sway is required to advance our understanding of nGVS.…”
Section: Discussionmentioning
confidence: 99%
“…While skin preparation and the skin/ electrode interface are paramount in electrical stimulation protocols, they are often unreported in the nGVS literature ( Table 3 ). The conductive interface between the electrode and skin is either a saline soaked sponge ( Wuehr et al, 2016a , b ; Nooristani et al, 2019b ; Eder et al, 2022 ) or electrode gel ( Mulavara et al, 2011 ; Goel et al, 2015 ; Mulavara et al, 2015 ; Samoudi et al, 2015 ; Temple et al, 2018 ; Ko et al, 2020 ; Piccolo et al, 2020 ; Asslander et al, 2021 ; Lotfi et al, 2021 ). Most nGVS machines measure impedance and will signal to the user if it becomes too high.…”
Section: Integrated Analysis and Discussionmentioning
confidence: 99%